Gibbs - Konovalov law. The cases of special points of biphase triple mixtures - O. B. Razova; T. V. Chelyuskina; L. A. Serafimov (Тонкие химические технологии)
The reasons of non-observance law of Gibbs - Konovalov in points binary azeotrops and pure components are revealed in case of a three-componental mixtures.